Managing the social aspects of software development ecosystems: An industrial case study on personality. Issue 11 (8th June 2020) - Akarsu, Zulal; Yilmaz, Murat
Abstract: The social aspects of software development encompass concerns such as motivating practitioners, building effective teams, and developing personal relations. Not surprisingly, perhaps, many software projects fail due to personality conflicts within team members. This study investigates the personality traits of 132 software practitioners by employing a tailored interactive assessment that was specifically developed for software development organizations. To assess the personality characteristics of the software teams as a whole, the results of 20 project teams were visualized by using personality–team radar charts. The validity part of the study was performed through validation interviews with experts from the field, discussing their experiences using the interactive assessment. The findings of this investigation complement those of earlier studies that suggest that productive team members who were working on social isolation showed higher introversion. In particular, this study strengthens the idea that agreeableness was observed in agile teams. Ultimately, the present data also highlight the existence of conscientiousness personalities in agile software development.